2013
DOI: 10.1186/1471-2458-13-727
|View full text |Cite
|
Sign up to set email alerts
|

High burden of hepatitis B infection in Northern Uganda: results of a population-based survey

Abstract: BackgroundWorldwide 2 billion people are exposed to hepatitis B infection, 350 million have chronic infection, 65 million in sub-Saharan Africa. Uganda is highly endemic with 10% national prevalence of hepatitis B infection, rates varying across the country from 4% in the southwest and 25% in the Northeast. Childhood vaccination was rolled out in 2002, the effect of which on the burden of hepatitis B has not been examined. We determined the prevalence and risk factors for hepatitis B infection in the Northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 14 publications
11
54
4
Order By: Relevance
“…The prevalence in the present study is comparable to 16.8% obtained in studies from Senegal (Diop-Ndiaye), and from Uganda ** Significant correlation at the threshold 0.01; * Significant correlation at the threshold 0.05; ALT: Alanine amino transaminase; AST: Aspartate amino transaminase; ALP: Alkaline Phosphatase CB = conjugated Bilirubin; CD4 = Cluster of differentiation 4. (Ochola et al, 2013). It is however lower, compared to 19% reported in Northwest Ethiopia (Yoannes et al, 2014) and 20.4% reported in Malawi (Nyirenda et al, 2008).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The prevalence in the present study is comparable to 16.8% obtained in studies from Senegal (Diop-Ndiaye), and from Uganda ** Significant correlation at the threshold 0.01; * Significant correlation at the threshold 0.05; ALT: Alanine amino transaminase; AST: Aspartate amino transaminase; ALP: Alkaline Phosphatase CB = conjugated Bilirubin; CD4 = Cluster of differentiation 4. (Ochola et al, 2013). It is however lower, compared to 19% reported in Northwest Ethiopia (Yoannes et al, 2014) and 20.4% reported in Malawi (Nyirenda et al, 2008).…”
Section: Discussioncontrasting
confidence: 46%
“…Previous studies in sub-Saharan Africa showed that HBV infection prevalence among HIV positive people varies from one region to another: from 17.5% in a hospital setting in Dar Es Salaam, Tanzania (Nagu et al, 2008), 17% in Northern Uganda (Ochola et al, 2013), 12.8% in the North-Eastern Nigeria (Obi et al, 2012), 12.6% in the North-West region of Cameroon (Zoufaly et al, 2012), to 12.2% in The Gambia (Jobarteh et al, 2010). However, in many setting, the dual infection HIV and Hepatitis B virus still goes unnoticed due to the lack of diagnostic means: The spread of this co-infection is rapid while diagnostics means are still deficient.…”
Section: Introductionmentioning
confidence: 99%
“…It is also one of the few studies in African sub Saharan region that includes sexually active youth and young adolescent groups. 60 years [22] and is lower than the 23.9% found by Emmanuel et al in 2013 in northern Uganda among the same age group as ours [23]. These high prevalence rates are probably due to difficult living conditions in rural areas and to the non-inclusion of hepatitis B vaccination programs in these countries before these studies [24,25].…”
Section: Discussioncontrasting
confidence: 54%
“…Emmanuel et al [23] have not found any significant difference according to age (p=0.575) either. Other studies have, on the other hand, reported that having an education which is less than A'level was a risk factor for the presence of serological markers of HBV [35,36].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation